Pengaruh Relaksasi Autogenik terhadap Tingkat Kecemasan dan Perubahan Tekanan Darah pada Pasien Riwayat Hipertensi - Ni Luh Putu Ekarini; Paula Krisanty; Suratun Suratun (Poltekkes Kemenkes Jakarta III, 2018)
Hypertension is one type of non-communicable disease, which is increasing every year. Hypertension is a condition where systolic blood pressure ≥ 140 mmHg and / or diastolic blood pressure ≥ 90 mmHg. Today the treatment of a disease including hypertension has been widely modified between pharmacological therapy and non-pharmacological therapy. One of the non-pharmacological therapies currently used is autogenic relaxation. Autogenic relaxation technique is one of the relaxation techniques that comes from ourselves in the form of words or short sentences or thoughts that can make the mind calm. Autogenic relaxation is done by imagining yourself in a state of peace and calm, focusing on regulating your breath and heartbeat. This study aims to determine the effect of autogenic relaxation on anxiety levels and changes in blood pressure in patients with hypertension history at Cipayung Health Center, East Jakarta. The research design used was a Quasi-experimental research design. The number of research samples is 58 respondents. The results showed that there were differences in systolic blood pressure (p = 0.000) and the anxiety level of respondents (p = 0.000) after autogenic relaxation interventions were performed.